phân tích đa thức thành nhân tử
xy(x+y)−2x−2y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,=x\left(x^2-2x+1-y^2\right)=x\left[\left(x-1\right)^2-y^2\right]=x\left(x-y-1\right)\left(x+y-1\right)\\ 2,=\left(x+y\right)^3\\ 3,=\left(2y-z\right)\left(4x+7y\right)\\ 4,=\left(x+2\right)^2\\ 5,Sửa:x\left(x-2\right)-x+2=0\\ \Leftrightarrow\left(x-2\right)\left(x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2\end{matrix}\right.\)
\(x^4+y^2-2x^2y+x^2+2x-2y\)
\(=\left(y^2-x^2y-xy\right)-\left(x^2y-x^4-x^3\right)+\left(xy-x^3-x^2\right)-\left(2y-2x^2-2x\right)\)
\(=y\left(y-x^2-x\right)-x^2\left(y-x^2-x\right)+x\left(y-x^2-x\right)-2\left(y-x^2-x\right)\)
\(=\left(y-x^2+x-2\right)\left(y-x^2-x\right)\)
a,\(A=x^3-2x^2=x^2\left(x-2\right)\)
\(b,\) \(y^2+2y-x^2+1=-x^2-xy-x+xy+y^2+y+x+y+1\)
\(=-x\left(x+y+1\right)+y\left(x+y+1\right)+\left(x+y+1\right)\)
\(=\left(-x+y+1\right)\left(x+y+1\right)\)
\(c,\) \(\left(x+1\right)^2-25=\left(x+1+5\right)\left(x+1-5\right)=\left(x+6\right)\left(x-4\right)\)
\(a,=6x\left(x-2\right)-7\left(x-2\right)=\left(6x-7\right)\left(x-2\right)\)
x2 + y2 + 2xy - 2x - 2y
= (x2 + 2xy + y2) - (2x + 2y)
= (x + y)2 - 2(x + y)
= (x + y)(x + y + 2)
xy(x+y)-2(x+y)
=(x+y)(xy-2)
Trả lời:
xy ( x + y ) - 2x - 2y
= xy ( x + y ) - ( 2x + 2y )
= xy ( x + y ) - 2 ( x + y )
= ( x + y ) ( xy - 2 )